1988
DOI: 10.1164/ajrccm/137.2.358
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Analysis of Household Dust Samples

Abstract: Household dust samples from the homes of 106 allergy clinic patients in Baltimore were analyzed for specific allergen content. Dust mite antigen content was determined by enzyme-linked immunosorbent assays (ELISA) specific for the major allergens of Dermatophagoides pteronyssinus, D. farinae, and D. microceras. Cat and dog antigen content were determined by ELISA using antisera for Fel d 1 (formerly cat allergen 1) and dog allergens 3 and 13, respectively. Mold content was assessed by culture with microscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(100 citation statements)
references
References 1 publication
11
86
3
Order By: Relevance
“…In contrast, several studies reported positive associations between total numbers of CFU and specific diseases such as bronchial asthma (9,24,25). The reason why we found little relationship was possibly because the sample size was small and non-specific diseases were investigated.…”
Section: Discussioncontrasting
confidence: 88%
“…In contrast, several studies reported positive associations between total numbers of CFU and specific diseases such as bronchial asthma (9,24,25). The reason why we found little relationship was possibly because the sample size was small and non-specific diseases were investigated.…”
Section: Discussioncontrasting
confidence: 88%
“…Mean household exposure to cat allergen Fel d 1 in patients with positive skin test responses to both mites and cats was 1.3 ~g/gm of fine dust, the levels that are usually found in homes without a cat. 31 It is unlikely that exposure to cat allergen at these levels was a significant confounding factor in the analysis of mite allergen exposure-response relationship in asthma activity. Another important factor that can influence the level of BHR is viral infection?…”
Section: Discussionmentioning
confidence: 99%
“…We then clarified extracts by centrifugation at 1,300 g and pipetted the supernatant into screw-top storage tubes, which we froze until needed. We measured the cockroach antigen Bla g 1 by a two-site, monoclonal antibody enzymelinked immunosorbent assay (ELISA) as described by Pollart et al (23); the dust mite allergens Der f 1 and Der p 1 and the cat allergen Fel d 1 using antigen-capture ELISA assays employing monoclonal capture and detector antibodies (24,25); the dog allergen Can f 1 using a monoclonal capture and polyclonal detector antibody protocol similar to those described by Schou et al (26) and Ingram et al (27); and the rat allergens according to previously published methods (28). We assayed MUP using purified antigen and a polyclonal rabbit anti-MUP antibody (Greer Laboratories, Inc., Lenoir, NC, USA) and goat anti-rabbit antibody (Sigma Chemical Co., St. Louis, MO, USA) in a competitive inhibition ELISA as described by Miller et al (29).…”
Section: Methodsmentioning
confidence: 99%